An epichromatin epitope: persistence in the cell cycle and conservation in evolution - Olins, Ada L.; Langhans, Markus; Monestier, Marc; Schlotterer, Andrea; Robinson, David G.; Viotti, Corrado; Zentgraf, Hanswalter; Zwerger, Monika; Olins, Donald E. (Nucleus, 2011)
Interphase nuclear architecture is disrupted and rapidly reformed with each cell division cycle. Successive cell generations exhibit a “memory” of this nuclear architecture, as well as for gene expression. Furthermore, many features of nuclear and mitotic chromosome structure are recognizably species and tissue specific. We wish to know what properties of the underlying chromatin structure may determine these conserved features of nuclear architecture. Employing a particular mouse autoimmune anti-nucleosome monoclonal antibody (PL2-6), combined with deconvolution immunofluorescence microscopy, we present evidence for a unique epitope (involving a ternary complex of histones H2A and H2B and DNA) which is localized only at the exterior chromatin surface of interphase nuclei and mitotic chromosomes in mammalian, invertebrate and plant systems. As only the surface chromatin region is identified with antibody PL2-6, we have assigned it the name “epichromatin”. We describe an “epichromatin hypothesis”, suggesting that epichromatin may have a unique evolutionary conserved conformation which facilitates interaction with the reforming post-mitotic nuclear envelope and a rapid return of interphase nuclear architecture.